The pharmacist’s role on transgender care: findings from a literature review - de Souza Pinho, Arthur Antunes (2022)
Transgender is a broad-spectrum term referring to people who do not match their assigned sex at birth. Several issues, including social detachment, poor access to healthcare services, and the lack of social/economic opportunities, have historically affected this population. In this scenario, pharmacists - not mentioned in national and international clinical guidelines/protocols regarding transgender care - might be key professionals to serve and care for this population. The main goal of this literature review was to identify the pharmacists’ role in the care of transgender people. The articles were retrieved from scientific databases. After applying filters (e.g., language, full-text availability, and coverage of the research question), seven articles were included in this review. The articles did not present pharmaceutical experiences or practices regarding transgender healthcare. Instead, some articles stressed the inadequate or inappropriate use of hormones and their side effects, also covering the role of this issue in professional development, gaps, and potential opportunities for research and pharmaceutical services. Pharmacists, included in a multi-professional team, could be a key element to promote access to healthcare and the well-being of the transgender population.